Psychological capital, academic buoyancy, academic major satisfaction, and academic adjustment during the pandemic - Safriani, Yuniar; Muhid, Abdul (Universitas Muhammadiyah Surakarta, 2022)
Abstract. The COVID-19 pandemic has impacted on the educational aspects of various levels of education, and several countries have shut schools nationwide affecting two-third of students worldwide. This change challenges the students who usually involved in face-to-face learning to switch to distance learning (online), and thus it influences their life as students and individuals. This study aims to determine the effect of psychological capital, academic buoyancy, and academic major satisfaction on academic adjustment of senior high school students during the COVID-19 pandemic. The subjects in this study were 145 students, taken by random sampling technique from the total population. The method used in this study was quantitative methods by using Structural Equation Modeling (SEM) analysis. Data collection employed was four scales: the psychological capital scale, academic buoyancy, academic major satisfaction, and the academic adjustment. The results of this study indicate that the R-Square value of the endogenous latent variable is 0.463, which means that the psychological capital, academic buoyancy, and academic major satisfaction variables have an influence on the academic adjustment variable of 46.3%. Thus, the hypothesis proposed in this study is accepted. Therefore, there is a significant positive effect of psychological capital, academic buoyancy, and academic major satisfaction on the academic adjustment of senior high school students during the COVID-19 pandemic. Keywords: psychological capital; academic buoyancy; academic major satisfaction; academic adjustment; senior high school students.